Identifying the relationship of colours and forms in affective design - Lee, Yong Quan. (2013)
Compared to early days of product inventions, current inventions face numerous challenges from many competitor firms. This is due to both the onset of globalization and the advancement in technology and science. Therefore, the priorities for modern design have changed, focusing not only on functions but also other abstract quantities. In addition, with more purchasing powers and choices in the market, consumers yearn to satisfy not only their need but also their wants. The ‘wants’ differ from individual to individual. Regardless, designer has to capture this ‘wants’ and to translate them into specifications and constraints, in other to create products that will capture the market demands and thrive among the competitors. One particular design process that is created for adapting in abstract, fuzzy logic environment is called ‘Kansei Engineering’. It was developed by Nagamachi in 1995 as an ergonomic, customer-orientated design process. This report will introduce about the definition and methods involved in a typical Kansei Engineering process. It will explain the need for such an engineering process in greater detail, and the steps to carry out a Kansei Engineering process. There will be a case study regarding a Kansei Engineering analysis on relationship between colour and form in affecting people’s emotion and perspective of the product. 3 analysis methods have been carried out for the semantic values of the different model form, and 1 analysis method has been carried out for the semantic values of the different model colour. The results has been generally conclusive, suggesting a particular feature will exude certain Kansei, in addition, the superposition of the analytical method creates a refined identification of primary feature contributing to a particular Kansei, and gradual features that contribute less but yet substantial towards the Kansei.